High frequency of enterovirus D68 in children hospitalised with respiratory illness in Norway, autumn 2014. Issue 2 (23rd December 2014) - Bragstad, Karoline; Jakobsen, Kirsti; Rojahn, Astrid E.; Skram, Marius K.; Vainio, Kirsti; Holberg‐Petersen, Mona; Hungnes, Olav; Dudman, Susanne G.; Kran, Anne‐Marte B.
<x xml:space="preserve">Abstract</x> Objectives An unexpectedly high proportion of children were admitted for severe respiratory infections at the Oslo University Hospital, Ullevål, Norway, during September and October, 2014. In light of the ongoing outbreak of enterovirus‐D68 (EV‐D68) in North America a real‐time RT‐PCR for screening of enterovirus and enterovirus D68 was established. Design We developed a duplex real‐time RT‐PCR for rapid screening of enterovirus D68. The method target the 5′ non‐translated region (NTR) of the HEV genome at a location generally used for enterovirus detection. Sample Nasopharyngeal samples (n = 354), from children <15 years of age, received for respiratory virus analysis in OUH during September 1st and October 31nd, 2014, were tested for enterovirus and screened for enterovirus D68. Main outcome measures and results The duplex real‐time RT‐PCR method was an efficient tool for rapid screening for EV‐D68 in respiratory specimens. Enterovirus was detected in 66 (22%) of 303 pediatric nasopharyngeal samples collected from children hospitalised with acute respiratory infection within the two‐month period. Out of these, 33 (50%) were EV‐D68. EV‐D68 was associated with acute flaccid paralysis in one child. Conclusions An unexpectedly high proportion of children admitted for severe respiratory infections at the Oslo University Hospital, Ullevål, Norway, were diagnosed with EV‐ D68 during September 1st and October 31nd, 2014. These results emphasise that greater vigilance is required throughout Europe as enteroviruses are cause of severe respiratory disease.